The Future of Strategy - Gray, Colin S. (Cambridge, UK ; Malden, MA : Polity, 2015)
"Strategy is not a modern invention. It is an essential and enduring feature of human history that is here to stay. In this original essay, Colin S. Gray, world-renowned scholar of strategic thought, discusses the meaning of strategy and its importance for politicians and the military as a means of achieving desired outcomes in complex, uncertain conditions. Drawing on a wide range of examples from the Great Peloponnesian War to the Second World War, Vietnam, and the ongoing conflicts in Iraq and Afghanistan, Gray ably shows how great military thinkers of the past and present have acted strategically in their various ideological, political, geographical and cultural contexts. Looking to the future, he argues that strategy will continue to provide a vital tool-kit for survival and security, but that the global threat posed by nuclear weapons remains an on-going challenge without obvious practical solutions. As Gray boldy asserts, there is no promised land ahead, only hard and dangerous times that will require us to master the theory and practice of strategy to secure our own future"--
Politics the master -- What is strategy and why does in matter? -- Theory and practice -- Strategic history: continuity and change -- Theory and practice -- Strategic history: continuity and change -- Strategy and geography -- Strategy and the future -- Conclusion.
Includes bibliographical references and index.
Keywords: Strategy; War (Philosophy); Nuclear warfare -- Prevention; Geopolitics; POLITICAL SCIENCE / Peace